2004
DOI: 10.1007/s00701-004-0293-5
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced thermotherapy of neoplastic lesions in the brain ? underlying tissue alterations, MRI-monitoring and clinical applicability

Abstract: Laser-induced thermotherapy (LITT) is a minimally invasive neurosurgical approach to the stereotactic treatment of brain tumors in poorly accessible regions. Its clinical applicability has been shown in several experimental and clinical studies under on-line monitoring by magnetic resonance imaging (MRI). This review characterizes LITT as an alternative neurosurgical approach with specific focus on the typical histological alterations and ultrastructural cellular changes following laser irradiation in the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…1,5,11,12 The LITT procedure can produce an acute gross-total ablation that immediately coagulates the entire enhancing portion of the tissue or induce short-term necrosis and apoptosis. 47,59,60,62 This has been observed radiographically as immediate central necrosis of the tumor. Furthermore, beyond the analogy of resection, preliminary animal studies in LITT have indeed shown that laser ablation acutely leads to breakdown of the BBB.…”
Section: Controversy Over Focal Therapy For Hggsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,11,12 The LITT procedure can produce an acute gross-total ablation that immediately coagulates the entire enhancing portion of the tissue or induce short-term necrosis and apoptosis. 47,59,60,62 This has been observed radiographically as immediate central necrosis of the tumor. Furthermore, beyond the analogy of resection, preliminary animal studies in LITT have indeed shown that laser ablation acutely leads to breakdown of the BBB.…”
Section: Controversy Over Focal Therapy For Hggsmentioning
confidence: 99%
“…3D), which is thought to represent a degradation of the surrounding BBB. 47,59,60,62 Subsequent effects vary depending on the tumor, the patient, and responses to LITT, which are described below.…”
Section: The Radiographic Effects Of Littmentioning
confidence: 99%
“…The real-time imaging mode is able to continuously monitor the position of the laser fiber in different planes. For therapy monitoring, advanced image processing software can be used during thermal ablation [7].…”
Section: Tumor Entity and Treatment Modalitiesmentioning
confidence: 99%
“…The primary lesion shows differences in lesion diameter corresponding to the irradiation time and thermal energy deposition to the tissue. The typical architecture of a laser lesion consists of a central coagulation necrosis which is not apparent immediately after irradiation but is demarcated by a surrounding rim of edema adjacent to undamaged tissue [7,8], visible in early MR controls and follow-ups. The necrosis becomes evident by a gradual loss of contrast medium enhancement (gadolinium, Gd) and early resorptive changes in the margins by day 3.…”
Section: Zones Of Lesionmentioning
confidence: 99%
See 1 more Smart Citation